Culture teaching in EFL classes: Teachers’ beliefs, attitudes, and classroom practices - Lucky Amatur Rohmani; Erna Andriyanti (Universitas Syiah Kuala, 2022)
It is inevitably believed that culture teaching is the pivotal feeling of integrating culture into the teaching of a language, including in the EFL setting. This study aims to explore the English teachers’ beliefs, attitudes, and the reflection of their beliefs and attitudes on the teaching syllabi. The sequential explanatory mix-methods design was applied in junior high schools in Ngawi. The data were obtained from 144 English teachers’ answers to a questionnaire and interviews with six teachers. Then, the data were analysed by using descriptive statistics, the independent sample T-test, and the Mann-Whitney test. The results indicated that the majority of junior high school English teachers believed in the importance of incorporating culture into their teaching of the language taught and students’ learning process. Moreover, both state and private junior high school English teachers showed similar beliefs and attitudes related to culture teaching. When they taught English, the culture associated with that language had also been taught so that the misconception of learning the language can be minimized. The result of teachers’ practices strongly indicates that the English teachers in Ngawi had implemented the teaching of culture and inserted various cultural elements in the process of their teaching and learning in the EFL classes.